Heterotopic Tourism and Cultural Revivalism of Dusun Community in Bundu Tuhan, Sabah, Malaysia - Nur Widiyanto (Metahumaniora, 2018)
AbstractThe paper discusses cultural movement of the Dusun community in Bundu Tuhan, Sabah, Malaysia and its connection to eco-tourism development in Kinabalu Park. The objective is to examine whether the involvement of the local people with the ecotourism through dominating the numbers of mountain guides and initiating the kakakapan id gayongaran (a traditional ceremony)are strategies to deal with the forces that culturally excludesthem from the ancestral land or merely spontaneously actions. Employing ethnographic studies through participant observation, it reveals that the Dusun people in Bundu Tuhan had successfully exercised the heteropic tourism through combining the involvement on mountain guiding and cultural events to obtain a bigger recognition toward the access Mount Kinabaluas their ancestral land. The outcomes are the two-day free access to the mountain every year and steady economic income earned through working at the Kinabalu Park.Keywords: dusun, heteropic, tourism, Kinabalu Park, ancestral landAbstrakPaper ini membahas gerakan cultural komunitas Dusun di Kampung Bundu Tuhan, Sabah, Malaysia dan kaitannya dengan eko-wisata di Taman Kinabalu. Tujuan riset ini adalah melihat apakah keterlibatan penduduk local dalam wisata alam melalui upaya mendominasi jumlah pemandu gunung dan menginisiasi ritual “kakakapan id gayongaran” merupakan strategi untuk bernegosiasi dengan kekuatan luar yang meminggirkan mereka secara budaya, atau sekedar tindakan yang bersifat spontan. Menggunakan metode etnografi melalui observasi lapangan, hasil studi menunjukkan bahwa orang Dusun di Bundu Tuhan berhasil menggunakan “heteropic tourism” dengan mengkombinasikan keterlibatan mereka dalam bisnis pemandu gunung dan menginisiasi event budaya untuk mendapatkan pengakuan atas akses yang lebih besar terhadap Gunung Kinabalu sebagai tanah adat mereka. Hasil yang diperoleh adalah akses selama 2 hari dalam satu tahun untuk melakukan ziarah gunung dan pada sisi lain tetap mendapatkan keuntungan ekonomi yang stabil dengan bekerja di Taman Kinabalu.Kata kunci: dusun, heteropic, wisata, Taman Kinabalu, tanah leluhur